DEVELOPMENT OF TIKTOK VIDEO BASED LEARNING MEDIA IN SOFTWARE APPLICATION SUBJECT FOR XII DPIB STUDENTS SMK ISLAM 1 BLITAR - Widiastuti, Fanny Iga; Isnandar, Isnandar; Aris Ichwanto, Muhammad (Jurnal Pensil : Pendidikan Teknik Sipil, 2024)
This research is motivated by the lack of use of interactive learning media in software application and interior design subjects. This study aims to develop efficient and interactive tiktok video-based learning media in order to help students more easily understand the learning material delivered by the teacher. This research uses the Research and Development (RnD) development model and the ADDIE research method which consists of 5 stages, namely Analysis, Design, Development, Implementation, and Evaluation. To determine the feasibility of this learning media, a design validity test was conducted by media experts, material experts, and users (students). The results of the media expert validity test get a value with very feasible criteria, as well as the results of the material expert validation get a value with very feasible media result validation criteria, the results of small group trials on students get a value with a percentage of 91.54%, then on the other hand the results of large group trials on students get a value with a percentage of 86.79%. Thus, Tiktok Video-Based Learning Media for XII DPIB Students of SMK Islam 1 Blitar in Software Application and Interior Design Subjects can be said to be feasible to use as supporting material in learning.